Implementation of Time-Driven Activity-Based Costing In an Education Service Company - Muharam Isnaeni; Taufik Faturohman (PT. Maju Malaqbi Makkarana, 2026)
This paper uses Time-Driven Activity-Based Costing (TDABC) in identifying cost per student, program profitability, and breakeven point across programs and branches at PT Kreasi Edulab Indonesia as it seek to solve the cost allocation issues that arise due to the differences in instructional hours, staffing activity, and resource usage in providing educational services. The study will employ a quantitative methodology in which they will formulate TDABC-based cost modelling and simulating models to assign operational costs to the real instructional time and teaching capacity. Primary data were gathered by direct observation and internal cost structure mapping, whereas the secondary data were in the form of financial records, class schedules, and student enrollment reports. The analysis combines descriptive statistics, TDABC simulations, program profitability analysis, breakeven analysis, and sensitivity analysis to measure the cost per student, program level operating performance, minimum viable class sizes, and how the major financial drivers influence the operating profit. The findings indicate significant differences in cost per student and profitability of programs and size of a branch with some branches having lower levels of profitability below sustainable levels of breakeven despite the similar levels of revenues. The sensitivity analysis shows that average revenue per student is the most sensitive variable of operating profit, over and above the fluctuations in the enrolment volume and cost structure. Altogether, the results indicate that TDABC contributes to the increase of cost transparency and offers a solid foundation to the pricing, class consolidation, and operational decision-making.